A new species of the genus Leptolalax (Anura, Megophryidae) from Hunan, China - Hou, Yinmeng; Zhang, Mengfei; Hu, Fei; Li, Siyuan; Shi, Shengchao; Chen, Jun; Mo, Xiaoyang; Wang, Bin (Zootaxa, 2018)
A new species, Leptolalax mangshanensis sp. nov., is described from the Mangshan National Nature Reserve, in Hunan Province, China. The new species is genetically similar to Leptolalax liui, and morphologically similar to Leptolalax maoershanensis. Morphological characteristics that distinguish the new species from its congeners are a small body size (snout-vent length, SVL, 22.2 mm–27.8 mm in 27 adult males, and 30.2 mm in one adult female); nearly smooth dorsal skin with some small, orange, tubercles and irregular, dark brown stripes, throat and belly scattered with white speckles, weak lateral fringes on toes and rudimentary toe webbing; indistinct longitudinal ridges under toes, and not interrupted at the articulations, iris bicolored with bright orange in the upper half and greyish cream in the lower half. The new species is widely distributed in montane evergreen secondary forests and small bamboo forests in Mangshan Nature Reserve, at altitudes between 500–1600 m a.s.l.